THE SYSTEM OF INDICATORS OF THE ECONOMIC EFFICIENCY OF LAND US E IN THE CONTEXT OF THE ACTIVITIES OF AGRICULTURAL ENTERPRISES OF VARIOUS FORMS OF MANAGEMENT Kunduzova Kumrikhon (World Economics and Finance Bulletin, 2022)
This article discusses the fact that the way of life of our people is shaped by agriculture and animal husbandry, the favorable conditions that nature has endowed with agriculture; The importance of the relationship of land to the main part of the population living in rural areas and the role of agriculture in the formation of their family budgets was studied and analyzed.
Keywords: agriculture; farming; land